University Calculus: Early Transcendentals (3rd Edition)

Published by Pearson
ISBN 10: 0321999584
ISBN 13: 978-0-32199-958-0

Chapter 1 - Section 1.6 - Inverse Functions and Logarithms - Exercises - Page 50: 60



Work Step by Step

$$e^{(x^2)}e^{(2x+1)}=e^t$$ $$e^{x^2+2x+1}=e^t$$ - Recall that as $e^x=e^a$, then $x=a$ So here we have: $$t=x^2+2x+1$$ $$t=(x+1)^2$$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.